2009
DOI: 10.1186/1741-7007-7-86
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the histone H2A.Z-1 and H2A.Z-2 isoforms in vertebrates

Abstract: BackgroundWithin chromatin, the histone variant H2A.Z plays a role in many diverse nuclear processes including transcription, preventing the spread of heterochromatin and epigenetic transcriptional memory. The molecular mechanisms of how H2A.Z mediates its effects are not entirely understood. However, it is now known that H2A.Z has two protein isoforms in vertebrates, H2A.Z-1 and H2A.Z-2, which are encoded by separate genes and differ by 3 amino acid residues.ResultsWe report that H2A.Z-1 and H2A.Z-2 are expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(123 citation statements)
references
References 67 publications
3
116
0
Order By: Relevance
“…We generated two Flp-In TM -3T3 cell lines stably expressing either H2A or H2A.Z tagged with the SNAP epitope. Consistent with previous observations (Bulynko et al, 2006;Dryhurst et al, 2009;Greaves et al, 2007;Rangasamy et al, 2004), both variants showed a similar nuclear distribution and neither accumulated at the PHC at steady-state levels in our model system (supplementary material Fig. S1A,B).…”
Section: Different Dynamics Of H2a and H2az Deposition At Phcsupporting
confidence: 80%
“…We generated two Flp-In TM -3T3 cell lines stably expressing either H2A or H2A.Z tagged with the SNAP epitope. Consistent with previous observations (Bulynko et al, 2006;Dryhurst et al, 2009;Greaves et al, 2007;Rangasamy et al, 2004), both variants showed a similar nuclear distribution and neither accumulated at the PHC at steady-state levels in our model system (supplementary material Fig. S1A,B).…”
Section: Different Dynamics Of H2a and H2az Deposition At Phcsupporting
confidence: 80%
“…The lack of any phenotypic effects when H2A.Z expression is knocked down in these cells could indicate that the residual amounts of H2A.Z are sufficient to sustain growth and differentiation of C2C12 cells. In addition, recent studies showed that there are in fact two isoforms of H2A.Z encoded by distinct genes (49,50). Because our shRNA specifically targets H2A.Z-1 but not the H2A.Z-2 isoform, it is a formal possibility that the H2A.Z-2 isoform in these cells is sufficient to compensate for the loss of H2A.Z-1 in these cells.…”
Section: Discussionmentioning
confidence: 94%
“…Z.2), another monophyletic lineage within H2A. 39,50,51 In both cases, the differentiation of specialized vertebrate variants is concomitant with an increase in organismal complexity, underscoring the role of these variants in refining chromatin structure and the associated epigenetic mechanisms. On the contrary, the apparent absence of macroH2A in some protostome groups (i.e., nematodes and holometabolous insects) indicates that this variant might not be indispensable for the correct development of all organisms.…”
Section: Discussionmentioning
confidence: 99%